2019
DOI: 10.3390/molecules24213838
|View full text |Cite
|
Sign up to set email alerts
|

Trash to Treasure: Eco-Friendly and Practical Synthesis of Amides by Nitriles Hydrolysis in WEPPA

Abstract: The hydration of nitriles to amides in a water extract of pomelo peel ash (WEPPA) was realized with moderate to excellent yields without using external transition metals, bases or organic solvents. This reaction features a broad substrate scope, wide functional group tolerance, prominent chemoselectivity, and good reusability. Notably, a magnification experiment in this bio-based solvent at 100 mmol further demonstrated its practicability.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 73 publications
0
3
0
Order By: Relevance
“…The water extract of pomelo peel ash (WEPPA) used in this study was firstly prepared according to our reported procedure [17] . Then, the reaction of N ‐methylindole 1 a and iodobenzene 2 a was selected as the model reaction to screen the best conditions (Table 1).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The water extract of pomelo peel ash (WEPPA) used in this study was firstly prepared according to our reported procedure [17] . Then, the reaction of N ‐methylindole 1 a and iodobenzene 2 a was selected as the model reaction to screen the best conditions (Table 1).…”
Section: Resultsmentioning
confidence: 99%
“…The water extract of pomelo peel ash (WEPPA) used in this study was firstly prepared according to our reported procedure. [17] Then, the reaction of N-methylindole 1 a and iodobenzene 2 a was selected as the model reaction to screen the best conditions (Table 1). This cross-coupling reaction preferred to occur at C-2 position of indole and formed 1methyl-2-phenyl-1H-indole 3 a as the major product in WEPPA (entry 1).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation